Facile synthesis of photolabile dendritic-unit-bridged hyperbranched graft copolymers for stimuli-triggered topological transition and controlled release of Nile red1. Issue 18 (14th May 2015) - Mo, Bin; Liu, Huanhuan; Zhou, Xiangdong; Zhao, Youliang
<x xml:space="preserve">Abstract</x> Successive RAFT SCVP and ROP were used to generate novel hyperbranched graft copolymers with the ability for the photo-triggered degradation and accelerative release of hydrophobic dye.